A New Assessment Parameter to Determine the Efficiency of a Hybrid Vehicle - Mahmoud, K. R. M.; Ghania, S. M. (Engineering, Technology & Applied Science Research, 2022)
This paper presents a new evaluation technique for determining the hybridization efficiency of a vehicle. First, the saving in fuel consumption is estimated in the ideal case considering the vehicle runs through a standard driving cycle and the engine runs at the lowest specific fuel consumption all the time. Subsequently, the hybridization efficiency can be defined as the ratio between the fuel savings in hybrid mode to the ideal savings according to the standard driving cycle. A case study was conducted with a medium-size passenger car according to the new European standard driving cycle. The results showed that the new proposed evaluation criterion is very effective for evaluating hybrid vehicles.